Alcohol Synthesis from CO2, H2, and Olefins over Alkali‐Promoted Au Catalysts—A Catalytic and In situ FTIR Spectroscopic Study. Issue 3 (14th December 2018) - Heyl, Denise; Kreyenschulte, Carsten; Kondratenko, Vita A.; Bentrup, Ursula; Kondratenko, Evgenii V.; Brückner, Angelika
Abstract: Au/TiO2 and Au/SiO2 catalysts containing 2 wt % Au and different amounts of K or Cs were tested for alcohol synthesis from CO2, H2, and C2 H4 /C3 H6 . 1‐Propanol or 1‐butanol/isobutanol were obtained in the presence of C2 H4 or C3 H6 . Higher yields of the corresponding alcohols were obtained over TiO2 ‐based catalysts in comparison with their SiO2 ‐based counterparts. This is caused by an enhanced ability of the TiO2 ‐based catalysts for CO2 activation, as concluded from in situ fourier‐transform infrared (FTIR) spectroscopy and temporal analysis of products (TAP) studies. The synthesized carbonate and formate species adsorbed on the support do not hamper CO2 conversion into CO and the hydroformylation reaction. The transformation of Au δ + to active Au 0 sites proceeds during an activation procedure. As reflected by CO adsorption and scanning transmission electron microscopy, the accessible Au 0 sites are influenced by the amount of alkali dopants and the support. FTIR data and TAP tests reveal a very weak interaction of C2 H4 with the catalyst, suggesting its quick reaction with CO and H2 after activation on Au 0 sites to form propanol and propane. Abstract : Au NPs and alkali dopants—an effective team : In situ FTIR spectroscopy and temporal analysis of products reveal the importance of the type of support and alkali‐metal dopant on the performance of Au NPs for CO2 adsorption and its conversion with H2 into C3 or C4 alcohols in the presence of C2 H4 or C3 H6 . The active Au 0 sites required for the activation of all feed components are generated by in situ reduction of Au δ + during an activation process.